Does cryoneurolysis result in persistent motor deficits? A controlled study using a rat peroneal nerve injury model. Issue 4 (29th January 2020) - Shah, Sameer B; Bremner, Shannon; Esparza, Mary; Dorn, Shanelle; Orozco, Elisabeth; Haghshenas, Cameron; Ilfeld, Brian M; Gabriel, Rodney A; Ward, Samuel
Abstract : Background: Cryoneurolysis of peripheral nerves uses localised intense cold to induce a prolonged block over multiple weeks that has the promise of providing potent analgesia outlasting the duration of postoperative pain following surgery, as well as treat other acute and chronic pain states. However, it remains unclear whether persistent functional motor deficits remain following cryoneurolysis of mixed sensorimotor peripheral nerves, greatly limiting clinical application of this modality. To help inform future research, we used a rat peroneal nerve injury model to evaluate if cryoneurolysis results in persistent deficits in motor function. Methods: Male Lewis rats (n=30) had their common peroneal nerves exposed bilaterally at the proximal lateral margin of the knee and subsequently underwent cryoneurolysis on one limb and sham treatment on the contralateral limb. Outcomes were evaluated on days 3, 14, 30, 90 and 180. The primary end point was motor function, based on ankle dorsiflexion torque. In addition, sensory function was tested based on von Frey's filament sensitivity to the peroneal sensory distribution. A subset of animals was sacrificed following functional testing at each time point, and general tissue morphology, connective tissue deposition, and axon counts were evaluated. Results: Motor deficits in treated limbs were observed at 3 and 14 days but had resolved at time points beyond 1 month. Bilateral sensory deficits were also observed at 3 and 14 days, and also resolved within 1 month. Consistent with motor functional deficits, axon counts trended lower in treated nerves compared with contralateral controls at 3 days; however, axon counts were not significantly different at later time points. Conclusions: When applied to a mixed sensorimotor nerve, cryoneurolysis did not result in persistent motor deficits.